Perkembangan Ilmu Falak Pada Peradaban Pra Islam - Mhd. Fikri Maulana Nasution (Universitas Islam Negeri Sumatera Utara, 2018)
This paper aims to explore the history of the glory of the development of astronomy before the Prophet Muhammad was sent to be an Apostle. Celestial science reached its golden age in the Abbasid period, where many astronomers were born, this is inseparable from the role of previous civilizations. Recorded several civilizations that existed before the prophet Muhammad were sent including some findings that contributed greatly to the development of astronomy, namely, civilization in the Mesopotamia region, Ancient Egypt and even the Arabs before the arrival of Islam. From these findings, it was developed by Islamic Atronomes such as al-Biruni, al-Khawarizmi, al-Khuzandi and others. This study uses qualitative methods, by analyzing the data relating to information on astronomy before the Apostle was sent to the friendship period and so on, then the data was collected so that the author found a collection of data on astronomy in the period before the Prophet Muhammad, sent. The findings that resulted from the study led to translation and research carried out by astronomers on the literature and this table of celestial sciences that brought astronomy to its peak